Whither commodity-based trade? - Rich, Karl M.; Perry, Brian D. (Wiley, 2011)
Market access for livestock products from Africa has traditionally been limited by the presence of certain infectious diseases that pose risks to animal and human health. However, an increasingly discussed option for widening that access is commodity-based trade (CBT) focusing on the health and safety attributes of the product rather than the disease status of the country of origin. There have, however, been few analyses on the potential economic impacts and unintended consequences of such an approach. This article examines the principles behind a dramatic shift in approach to trading opportunities that CBT might bring, exploring both technical and economic considerations.